Dampak Penggunaan Media Sosial dan Kesehatan Mental Remaja - Andi Tahir (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the impact of social media use on adolescents’ mental health. Along with the increasing popularity of social media, adolescents have become the most vulnerable group to its psychological effects. This research employed a quantitative approach through a survey of 300 adolescents aged 13–18 in Indonesia, who actively use platforms such as Instagram, TikTok, and Twitter. The results indicate that excessive use of social media is associated with increased symptoms of anxiety, depression, and low self-esteem. Factors such as duration of use, negative interactions, and exposure to harmful content are identified as the main determinants of these negative effects. On the other hand, the study also found that healthy use of social media, such as communicating with friends or following educational content, can have positive effects on mental health. Therefore, time management and careful selection of accessible content on social media are key to minimizing negative impacts and optimizing its benefits.